Peran Etnis Toraja dalam Pelestarian Bentuk Arsitekstur Rumah Tongkonan di Tengah Arus Globalisasi - Lidia Rettang; Syamsu Kamaruddin; A. Octamaya Tenri Awaru (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Tongkonan is the traditional house of the Toraja ethnic group, carrying profound social, symbolic, and spiritual values. In the face of globalization which increasingly threatens the existence of local cultures Tongkonan faces significant challenges in its preservation. This study aims to identify the role of the Toraja ethnic community in preserving the architectural form of Tongkonan, as well as to analyze the strategies they employ to address modernization. A qualitative research method was used with a case study approach conducted in North Toraja Regency, South Sulawesi. Data collection techniques included interviews, observation, and documentation involving traditional leaders, Tongkonan owners, woodcarvers, and local government institutions. The findings reveal that the preservation of Tongkonan involves not only the physical maintenance of the structure but also the intergenerational transmission of cultural values, participation in customary rituals, and engagement of the younger generation. Using structural functionalism theory, Tongkonan is understood as an integral part of the social structure that functions to maintain balance, cohesion, and the cultural identity of Torajan society. Governmental support further strengthens these preservation efforts